Paradoxes of the Presidency - Perlman, Daniel H.; American Association for Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
The many paradoxes of the profession of the college president are discussed, with focus on whether the presidency is a profession to which a person should aspire and can prepare. Some people feel the position of presidency should only be filled by people with a love of scholarship and the intellectual life. The expectation, especially at the more prestigious institutions, is that the best candidates will be reluctant to leave their scholarship or the satisfaction of other pursuits for anything as mundane and messy and manipulative as university management. A college or university president is suddenly thrust into a larger than life role and invested with great authority, but nowhere in the world of scholarship does a person learn how to be a public figure (though the position requires the skills of a political leader, corporate executive, and evangelist). Although the president is seemingly the person with the greatest power and authority in the university, he/she loses the power to speak off the record without others assuming that a message is being conveyed. It is a no-win situation when there is a weak president or presidency, but when it happens, the board of trustees moves in from one side and the deans from the other, and neither side really benefits. Once the board and deans become accustomed to the power, it is very hard to change their behavior, even by replacing the weak president. Before accepting the position of presidency, it is necessary to ask some ethical and practical questions and do some soul searching. It is important that a person's style as president be congruent with his/her personality. (SM)
Availability: American Association for Higher Education, One Dupont Circle, Suite 600, Washington, DC 20036 ($3.50 per back issue).
Educational level discussed: Higher Education.
AAHE Bulletin, v42 n2 p3-6 Oct 1989.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Qualifications; Administrator Role; College Administration; College Presidents; Higher Education; Leadership Qualities; Power Structure; Professional Autonomy; Opinion Papers; Journal Articles